Delay-dependent generalized h2 control for discrete T-S fuzzy large-scale stochastic systems with mixed delays - Li, Jiangrong; Li, Junmin; Xia, Zhile (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the problem of stochastic stability and generalized H2 control for discrete-time fuzzy largescale stochastic systems with time-varying and infinite-distributed delays. Large-scale interconnected systems consist of a number of discrete-time interconnected Takagi?Sugeno (T-S) subsystems. First, a novel Delay-Dependent Piecewise Lyapunov-Krasovskii Functional (DDPLKF) is proposed, in which both the upper and the lower bound of delays are considered
Keywords: fuzzy large-scale stochastic system; delay-dependent; generalized H2 control; infinite-distributed delays; linear matrix inequality